Web-Based Accounting Learning Innovation with Real-Time Journaling Simulation - Putri, Julianti; Intan, Lembayung; Nurmaesah, Nunung; Sumarna, Agus (Institut Teknologi dan Bisnis Bina Sarana Global, 2025)
Entering the era of globalization, education has undergone many changes. Education today is far more advanced than in the past, which was more conventional and did not yet utilize technology, resulting in many difficulties in accessing new knowledge. Now, technology has brought many innovations and new breakthroughs in learning media, one of which is the innovation of website-based accounting learning with real-time journaling simulations created by researchers. Researchers used literature studies to facilitate researchers in collecting data and UML (Unified Modeling Language) as a system design method that made it easier for researchers to create an overview of the running system. The ADDIE method (Analysis, Design, Development, Implementation, and Evaluation) was also applied as a method for system design and systematic development of educational systems. With this method, researchers can create learning media that makes it easier for users to learn accounting journaling and financial reporting. In addition, researchers hope that users can better understand journaling through the system that has been created.